Incidence, prevalence, and management of MRSA bacteremia across patient populations—a review of recent developments in MRSA management and treatment - Hassoun, Ali; Linden, Peter K.; Friedman, Bruce (Critical care (London, England), 2017)
Methicillin-resistant Staphylococcus aureus (MRSA) infection is still a major global healthcare problem. Of concern is S. aureus bacteremia, which exhibits high rates of morbidity and mortality and can cause metastatic or complicated infections such as infective endocarditis or sepsis. MRSA is responsible for most global S. aureus bacteremia cases, and compared with methicillin-sensitive S. aureus , MRSA infection is associated with poorer clinical outcomes. S. aureus virulence is affected by the unique combination of toxin and immune-modulatory gene products, which may differ by geographic location and healthcare- or community-associated acquisition. Management of S. aureus bacteremia involves timely identification of the infecting strain and source of infection, proper choice of antibiotic treatment, and robust prevention strategies. Resistance and nonsusceptibility to first-line antimicrobials combined with a lack of equally effective alternatives complicates MRSA bacteremia treatment. This review describes trends in epidemiology and factors that influence the incidence of MRSA bacteremia. Current and developing diagnostic tools, treatments, and prevention strategies are also discussed.